Old or new territory? Perspectives On Diversity, Inclusion and Belonging - Alluri, Rina Malagayo; Yéré, Henri-Michael (Autonomy and Responsibility Journal of Educational Sciences, 2022)
This article aims to question the concepts of diversity and inclusion by reflecting on the historical political traditions that have enabled the emergence of the practice in different societal contexts. This contribution situates diversity and inclusion in its origins from rights-based theories and practices such as global decolonization processes, the U.S. civil rights movement, critical race theory, and intersectionality. It then uses an autoethnographic methodology coupled with Yuval-Davis’ framework of ‘belonging’ to reflect on the authors’ experiences of doing PhDs in a global higher education programme. The article aims to provide both theoretical and autoethnographic insights into reflecting on the politics of identity within diversity, inclusion, and belonging (DIB). By using the authors’ diverse experiences as a valuable source of data, the article aims to reassert agency and complexity in diversity practice.